Elbow Dislocation with Ipsilateral Radial Shaft Fracture – A Case Report - Aita, Marcio Aurelio; Oliveira, Ricardo Kaempf de; Praetzel, Rafael Pêgas; Towata, Fernando; Delgado, Pedro Jose; Marques, Fabiano da Silva (Revista Iberoamericana de Cirugía de la Mano, 2019)
Background Posterior dislocation of the elbow associated to a radial shaft fracture is a rare lesion, its treatment is difficult and complicated, and the indications, surgical options, and timing of surgery may vary. In the present case, we performed immediately after the trauma (urgent care) an open reduction internal fixation (ORIF) surgery of the radial fracture by means of a 3.5 mm locking plate, associated to closed elbow reduction and stabilization with dynamic bracing.Case Report A 26-year-old woman was seen in our service with a traumatic deformity of her right, dominant forearm and elbow after a fall from a balance board and presented with a radial shaft fracture and posterior elbow dislocation. The palmar approach was used and the shaft fracture was fixated. During the radial fracture reduction maneuver, the dislocation of the elbow was spontaneously reduced. At 1 year postoperatively, the patient showed good wrist, forearm, and elbow range of motion (ROM). Disabilities of the arm, shoulder and hand (DASH) score of 5, visual analogue scale (VAS) of 0, and grip strength of 92%, as compared with the nonaffected side.Clinical Relevance Nowadays, case reports of concomitant, ipsilateral multiple injuries that uncommonly occur together in a single traumatic episode are very rare. The awareness of this association for early recognition is of paramount significance for ideal clinical results.
Keywords: dislocations; elbow joint; fractures; bone; radial fractures